Hard X‐ray ptychography at Taiwan Photon Source at 11–20 nm spatial resolution. (13th September 2021) - Tsai, Yi-Wei; Lin, Jhih-Min; Chen, Chun-Yu; Chen, Ying; Lin, Bi-Hsuan; Yin, Gung-Chian; Tang, Mau-Tsu; Huang, Yu-Shan
Abstract : The working of the hard X‐ray ptychography technique at Taiwan Photon Source, with 11–20 nm spatial resolution, is demonstrated. Experimental conditions influencing the results are also discussed. Abstract : X‐ray ptychography, a technique based on scanning and processing of coherent diffraction patterns, is a non‐destructive imaging technique with a high spatial resolution far beyond the focused beam size. Earlier demonstrations of hard X‐ray ptychography at Taiwan Photon Source (TPS) using an in‐house program successfully recorded the ptychographic diffraction patterns from a gold‐made Siemens star as a test sample and retrieved the finest inner features of 25 nm. Ptychography was performed at two beamlines with different focusing optics: a pair of Kirkpatrick–Baez mirrors and a pair of nested Montel mirrors, for which the beam sizes on the focal planes were 3 µm and 200 nm and the photon energies were from 5.1 keV to 9 keV. The retrieved spatial resolutions are 20 nm to 11 nm determined by the 10–90% line‐cut method and half‐bit threshold of Fourier shell correlation. This article describes the experimental conditions and compensation methods, including position correction, mixture state‐of‐probe, and probe extension methods, of the aforementioned experiments. The discussions will highlight the criteria of ptychographic experiments at TPS as well as the opportunity to characterize beamlines by measuring factors such as the drift or instability of beams or stages and the coherence of beams. Besides, probe functions, the full complex fields illuminated on samples, can be recovered simultaneously using ptychography. Theoretically, the wavefield at any arbitrary position can be estimated from one recovered probe function undergoing wave‐propagating. The verification of probe‐propagating has been carried out by comparing the probe functions obtained by ptychography and undergoing wave‐propagating located at 0, 500 and 1000 µm relative to the focal plane.